Pharmacodynamics and pharmacokinetics of lidocaine in a rodent model of diabetic neuropathy - Ten Hoope, Werner; Picardi, Susanne (Anesthesiology, 2018)
Background:Clinical and experimental data show that peripheral nerve blocks last longer in the presence of diabetic neuropathy. This may occur because diabetic nerve fibers are more sensitive to local anesthetics or because the local anesthetic concentration decreases more slowly in the diabetic ner
Gesehen am 13.05.2019